EFFECTIVE AND EFFICIENT MODELS OF ZAKAT MANAGEMENT: NORMATIVE AND INNOVATION BASE - Muslimin, JM (Jurnal Syarikah : Jurnal Ekonomi Islam, 2019)
Zakat is a social mechanism and system outlined in the teachings of Islam to be a path to inner well-being through equitable access to economic resources and togetherness. Unfortunately, often in practice, zakat is only a charitable mechanism. based on mercy and individual volunteerism. This paper wants to emphasize that traditions and thoughts that interpret zakat only as a charity process must be changed. One of them is to do a philosophical normative basic reorientation towards strengthening the stem and the model of zakat which is effective and efficient. This last thing is not only an abash to strive for, but also a necessity. Exposure is done by normative and deductive juridical methods. Combined with a systemic approach that refers to the standardization of organizations and models of social movements that are effective and efficient. The data is extracted from various sources of Islamic law literature then combined with architectural framework theory to find an effective and efficient organizing model. This research is a juridical research that is qualitative, where the researcher will describe and analyze from the data and other literature related to this research in a deductive way . In conducting the analysis, the author uses two approaches: a normative juridical approach and a paralellism setting to the basic theory of efficiency and effectiveness. Thus, to propose a model of innovation based on justified norms